2013
DOI: 10.21273/horttech.23.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Strawberry Nutrient Optimum Ranges through Diagnosis and Recommendation Integrated System Analysis

Abstract: Diagnosis and recommendation integrated system (DRIS) leaf blade and petiole optimum nutrient ranges were developed through tissue sampling in 53 commercial strawberry (Fragaria ×ananassa) fields in the coastal valleys of central California in 2010 and 2011. All fields were in an annual production system using the day-neutral cultivar Albion. Leaf blades and petioles were sampled five times from early flowering through the fruit harvest period. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“…Leaf blade N concentration for the proprietary cultivar was significantly affected by fertilizer rate at the 2 February and 4 April sampling (Table 4). Although there were oscillations of total N in leaf blade among sampling dates and treatments for both cultivars, all values measured in this study fell within ranges considered optimum or ideal for strawberry production (Bottoms et al., 2013), as shown in Table 6. The fact that the low fertilizer rates still had leaf blade N concentrations within optimum ranges may be explained by differences in cultivar between the two studies.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Leaf blade N concentration for the proprietary cultivar was significantly affected by fertilizer rate at the 2 February and 4 April sampling (Table 4). Although there were oscillations of total N in leaf blade among sampling dates and treatments for both cultivars, all values measured in this study fell within ranges considered optimum or ideal for strawberry production (Bottoms et al., 2013), as shown in Table 6. The fact that the low fertilizer rates still had leaf blade N concentrations within optimum ranges may be explained by differences in cultivar between the two studies.…”
Section: Resultssupporting
confidence: 61%
“…Since cultivars are often replaced in a few years, this may suggest limitations to the use of leaf blades analysis for assessing plant N status. Even with N levels within ranges considered ideal for strawberry production in California (Bottoms et al., 2013), CN9‐L and AN20‐L showed considerably lower values than all other treatments at most sampling dates. Although leaf blade N values of the Fronteras cultivar for CN9‐O and AN20‐O stayed mostly between the values of the respective low and the high rates, this trend was not observed for the proprietary cultivar.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, total N was more reliable for measuring plant N status. Bottoms et al [15] also found that NO 3 -N in the petiole was highly variable and did not reliably indicate the N status of the plants in high-yielding strawberry fields in California.…”
Section: Discussionmentioning
confidence: 98%
“…In an early study in California, N decreased from 2.3% to 1.9% from mid-June to early September in one cultivar but was relatively stable, varying from 1.8% to 2.1% in a second cultivar [14]. In a later study in California, N decreased from early flowering to the main harvest and then was stable [15]. Maximum values were about 3.3%, and minimum values were about 2.8%.…”
mentioning
confidence: 99%
“…DRIS evaluation has been used and conducted on different horticultural crops (Angeles et al, 1993;Beverly, 1991;Bottoms et al, 2013;Hartz et al, 2007). However, information concerning tomato crops in this area is limited, but some DRIS norms in tomato have been conducted by different authors in others countries (Abd El-Rheem et al, 2015; Caront and Parent, 1989;Hartz et al, 1998).…”
mentioning
confidence: 99%